التموين و الدعم الدادي للثورة الجزائرية - فطحيزة على,عبد الباقي; طواهرية ,علي; بالضياف, سليم (University of Eloued جامعة الوادي, 2024)
لقد بدأ التحضير و التموين للثورة الجزائرية منذ تأسيس المنظمة الخاصة سنة 1947 وكان التموين و الدعم يتمثل في الأسلحة و المؤونة و الذخيرة بحيث يعتبر الشعب الجزائري هو المصدر الأساسي لهذا الدعم في الداخل وقد قدم للثورة كل ما يملك وأما مصادر هذا التموين فقد تنوعت بين الضرائب و التبرعات و الزكاة والغنائم تم تحصيلها من العدو. وأما الدعم والتموين في الخارج فقد كان للجالية الجزائرية بالمهجر دور كبير في ذلك خاصة في الجانب المالي نتيجة اشتراكات ومساهمات فردية. كما كان للدول العربية دور هام في هذا التموين وخاصة البلدان المغاربية التي اعتبرت قواعد خلفية للثورة التحريرية و مناطق تجميع وعبور للسلاح. كما ساهمت بعض الدول الأجنبية في هذا الدعم و التموين. The preparation and supply of the Algerian revolution began since the establishment of the special organization in 1947 and the supply and support is in weapons, supplies and ammunition so that the Algerian people is the main source of this support at home has provided the revolution with everything he owns and the sources of this supply have varied between taxes, donations, zakat and spoils were collected from the enemy. With regard to support and supplies abroad, the Algerian diaspora has played a major role in this, especially in the financial aspect, as a result of individual contributions and contributions. The Arab countries also played an important role in this supply, especially the Maghreb countries, which were considered rear bases for the liberation revolution and as areas for the collection and transit of weapons. Some foreign countries have also contributed to this support and supply.
1954-1962م
Keywords: الدعم المادي; التموين للثورة; المنظمة الخاصة; الجالية الجزائرية; Supply for the revolution; private organization; Algerian community